Beyond Outbreaks: Media Coverage of Communicable and Cardiovascular Diseases in Nigeria - Samuel, Achor Apeh (Darul Yasin Al Sys, 2025)
Health communication research in Nigeria has largely prioritized communicable diseases such as cholera, polio, Lassa fever, and COVID-19, while non-communicable diseases (NCDs), particularly cardiovascular diseases (CVDs), receive comparatively limited scholarly and media attention. This conceptual paper interrogates the imbalance in media coverage between communicable and non-communicable diseases, drawing on agenda-setting theory to explain how the prioritization of outbreak-driven illnesses shapes public awareness, policy discourse, and resource allocation. While acknowledging the urgency of communicable diseases due to their epidemic potential, the paper argues that the neglect of CVDs in media narratives undermines long-term public health education, preventive measures, and sustained investment in NCD management. By synthesizing insights from global and Nigerian scholarship, the analysis demonstrates how crisis-oriented framing perpetuates a reactive rather than preventive health culture. Conceptually comparing communicable diseases and CVDs, the paper advances a framework for balanced health reportage that integrates outbreak response with consistent attention to lifestyle-related risks. It concludes by recommending that Nigerian media, scholars, and policymakers recalibrate health communication strategies to ensure proportional visibility for CVDs and other NCDs alongside infectious diseases.